2013
DOI: 10.1136/gutjnl-2012-303434
|View full text |Cite
|
Sign up to set email alerts
|

A genome wide association study of genetic loci that influence tumour biomarkers cancer antigen 19-9, carcinoembryonic antigen and α fetoprotein and their associations with cancer risk

Abstract: This study identified several loci associated with CA19-9, CEA and AFP concentrations. The ABO variants were associated with risk of OSCC and pancreatic cancers and AFP variants with risk of hepatocellular cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
64
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 71 publications
(71 citation statements)
references
References 44 publications
6
64
1
Order By: Relevance
“…Out of these 17 SNPs, four SNPs were also trait-associated SNPs in the Asian population, which was significantly enriched in the Han Chinese eQTLs (p=0.0009) (see online supplementary table S3). Examples here included rs12506899 located in the α-fetoprotein gene ( AFP ), that was significantly associated with the cancer antigen 19-9 (CA19-9) in a GWAS conducted in a Han Chinese population 22. In our data this SNP was significantly associated with AFP gene expression (p=1.42×10 −10 ).…”
Section: Resultsmentioning
confidence: 55%
“…Out of these 17 SNPs, four SNPs were also trait-associated SNPs in the Asian population, which was significantly enriched in the Han Chinese eQTLs (p=0.0009) (see online supplementary table S3). Examples here included rs12506899 located in the α-fetoprotein gene ( AFP ), that was significantly associated with the cancer antigen 19-9 (CA19-9) in a GWAS conducted in a Han Chinese population 22. In our data this SNP was significantly associated with AFP gene expression (p=1.42×10 −10 ).…”
Section: Resultsmentioning
confidence: 55%
“…Therefore, this study was conducted in two phases: at phase one, a genome-wide association study was conducted to identify the loci associated with the serum level of CEA in healthy Chinese men from a cohort that participated in the Fangchenggang Area Male Health and Examination Survey (FAMHES) (this part has been merged with other cohorts and partly published elsewhere [10], [11]). At phase two, the association between candidate SNPs found from phase one GWAS and preoperative CEA levels and prognosis of patients with CRC was analyzed.…”
Section: Introductionmentioning
confidence: 99%
“…These genotypes were recently shown to strongly affect CA19-9 levels in PSC patients and influence the diagnostic performance of CA19-9. 7 Although two recent GWAS have reported an association between FUT2 and CEA, 9,17 in this study we have shown for the first time that this association is clinically relevant and that it positively influences the diagnostic performance of CEA. Our results showed that CEA levels increased with the number of A alleles in the case of the rs601338 variant of FUT2.…”
Section: Discussionmentioning
confidence: 87%
“…8 A recent genome-wide association study (GWAS) revealed an association between serum CEA levels and genes for fucosyltransferases and AB0 blood group. 9 The enzymes FUT2 and FUT3 are capable of catalyzing the fucosylation of glycoproteins. Both enzymes are known for their importance in synthesizing CA19-9.…”
Section: Introductionmentioning
confidence: 99%